The Hazards of Starting and Quitting Smoking: Some Australian Evidence - Kidd, M.; Hopkins, Sandra (The Economic Society of Australia, 2004)
The empirical analysis employs individual level data from the Australian Health Survey combined with retrospective data on tobacco price matched to the age at which the individual started and quit smoking. Split-population hazard models are estimated for both starting and quitting smoking. The analysis suggests price plays a significant role in the decision to start smoking but not in the decision to quit. Further sensitivity analysis of different age groups and an alternative data source, questions the robustness of the significant role of price in the smoking initiation decision. From a policy perspective, the results indicate that increases in tobacco taxation can be an important instrument in reducing the incidence of smoking, but should be combined with other mechanisms such as mandating smoke-free environments and antismoking education. Our results strongly support the targeting of antismoking campaigns towards teenagers.